Robotic breast surgery: the pursue for excellence in treatment and satisfaction – a review - Clarke, Paula; Pires, Douglas de Miranda; Sá, Nayara Carvalho de; Cavalcante, Jessica Moreira; Oliveira, Fernanda Silveira de (Mastology, 2020)
1. Urban C, Lima R, Schunemann E, Spautz C, Rabinovich I, Anselmi K. Oncoplastic principles in breast conserving surgery. The Breast. 2011;20(Suppl. 3):S92-S95. https://doi. org/10.1016/s0960-9776(11)70302-2 2. Hinton C, Doyle P, Blamey R, Davies C, Holliday H, Elston C. Subcutaneous mastectomy for primary operable breast cancer. Br J Surg. 1984;71(6):469-72. https://doi.org/10.1002/ bjs.1800710623 3. Toth B, Lappert P. Modified skin incisions for mastectomy: the need for plastic surgical input in preoperative planning. Plast Reconstr Surg. 1991;87(6):1048-53. https://doi. org/10.1097/00006534-199106000-00006 4. Kroll S, Schusterman M, Tadjalli H, Singletary S, Ames F. Risk of recurrence after treatment of early breast cancer with skinsparing mastectomy. Ann Surg Oncol. 1997;4:193-7. https://doi. org/10.1007/BF02306609 5. Viegas JF, Lichtenfels M, de Souza ABA, Vollbrecht B, Laitano Neto F, Zerwes FP, et al. Aesthetic outcome and oncological safety of nipple-sparing mastectomy. Mastology. 2019;29(1):3-8. https://doi.org/10.29289/259453 9420190000418 6. Leff D, Vashisht R, Yongue G, Keshtgar M, Yang G, Darzi A. Endoscopic breast surgery: where are we now and what might the future hold for video-assisted breast surgery? Breast Cancer Res Treat. 2011;125:607-25. https://doi.org/10.1007/ s10549-010-1258-4 7. Toesca A, Peradze N, Manconi A, Galimberti V, Intra M, Colleoni M, et al. Robotic nipple-sparing mastectomy for the treatment of breast cancer: Feasibility and safety study. The Breast. 2017;31:51-6. http://dx.doi.org/10.1016/j. breast.2016.10.009 REFERENCES 8. Toesca A, Peradze N, Galimberti V, Manconi A, Intra M, Gentilini O, et al. Robotic Nipple-sparing Mastectomy and Immediate Breast Reconstruction With Implant: First Report of Surgical Technique. Ann Surg. 2017;266(2):e28-30. https:// doi.org/10.1097/SLA.0000000000001397 9. Sarfati B, Struk S, Leymarie N, Honart JF, Alkhashnam H, Fremicourt KT, et al. Robotic Prophylactic Nipple- Sparing Mastectomy with Immediate Prosthetic Breast Reconstruction: A Prospective Study. Ann Surg Oncol. 2018;25:2579-86. https://doi.org/10.1245/s10434-018-6555-x 10. Lai HW, Wang CC, Lai YC, Chen CJ, Lin SL, Chen ST, et al. The learning curve of robotic nipple sparing mastectomy for breast cancer: An analysis of consecutive 39 procedures with cumulative sum plot. Eur J Surg Oncol. 2019;45(2):125-33. https://doi.org/10.1016/j.ejso.2018.09.021 11. Sarfati B, Honart J, Leymarie N, Kolb F, Rimareix F. Robotic-assisted Nipple Sparing Mastectomy: A feasibility study on cadaveric models. J Plast Reconstr Aesthet Surg. 2016;69(11):1571-2. https://doi.org/10.1016/j.bjps.2016.08.007 12. Houvenaeghel G, Bannier M, Rua S, Barrou M, Heinemann A, Troy E, et al. Breast cancer robotic nipple sparing mastectomy: evaluation of several surgical procedures and learning curve. World J Surg Oncol. 2019;17. https://doi.org/10.1186/s12957-019-1567-y 13. Park HS, Kim JH, Lee DW, Song SY, Park S, Kim SI, et al. Gasless Robot-Assisted Nipple-Sparing Mastectomy: A Case Report. J Breast Cancer. 2018;21(3):334-8. http://dx.doi.org/10.4048/ jbc.2018.21.e45 14. Rajappa SK, Mch RK, Garg S, Ram D. Robotic nipple‐sparing mastectomy: The first experience from Indian subcontinent. The Breast J. 2018;24(6):1114-5. https://doi.org/10.1111/tbj.13146 Three-dimensional high resolution optics allow excellent dissection planes. Image magnification and intense lighting increase contrast of colors and visibility of structures, making dissection of the gland and recognition of all structures, especially blood vessels, more precise, thus reducing bleeding and preserving circulation to the nipple areolar complex. High precision movement, stability due to tremor elimination, articulation and motion of instruments enable good mobility around the curvature of the breast cupola7,9,10. Complication rates for RNSM are low (23%), mostly minor ones, with only 3% of conversion and 4% of reoperations. Ischemia and necrosis are rare (5%), and no total skin or NAC necrosis were reported. There are no studies so far that analyze cost-effectiveness for robotic breast surgeries, but the fast learning curve helps to reduce operating room time and consequently the costs. Robotic instruments are known to be expensive, so as maintenance for the robot, but strategies have been proposed to reduce costs17 and soon new competitors for the Da Vinci are expected to enter the robotic market20. In the search for increasingly less invasive surgeries, robotics seems to meet what is proposed without compromising oncological safety and keeping up with high-satisfaction aesthetic results. Longer follow-up and cost-effective analyzes will determine if this technique will be consolidated. AUTHORS’ CONTRIBUTION P.C. : Conceptualization, Data curation, Formal analysis, Project administration, Writing – original draft. D.M.P. : Conceptualization; Project administration, Writing – review & editing. N.C.S.: Conceptualization, Data curation; Writing – review & editing. J.M.C. : Investigation, Visualization. F.S.O. : Methodology; Visualization. 7 Robotic breast surgery: The pursue for excellence in treatment and satisfaction – a review Mastology 2020;30:e20190015 15. Dindo D, Dermatines N, Clavien PA. Classification of Surgical Complications A New Proposal With Evaluation in a Cohort of 6336 Patients and Results of a Survey. Ann Surg. 2004;240(2):205- 13. http://doi.org/10.1097/01.sla.0000133083.54934.ae 16. Warren H, Dasgupta P. The future of robotics. Investig Clin Urol. 2017;58(5):297-8. http://dx.doi.org/10.4111/icu.2017.58.5.297 17. Nayeemuddin M, Daley S, Ellsworth P. Modifiable Factors to Decrease the Cost of Robotic-Assisted Procedures. AORN J. 2013;98(4):343-52. https://doi.org/10.1016/j.aorn.2013.08.012 18. Childers C, Gibbons M. Estimation of the Acquisition and Operating Costs for Robotic Surgery. JAMA. 2018;320(8):835-6. https://doi.org/10.1001/jama.2018.9219 19. Khorgami Z, Li WT, Jackson TN, Howard A, Sclabas G. The cost of robotics: an analysis of the added costs of robotic-assisted versus laparoscopic surgery using the National Inpatient Sample. Surg Endosc. 2019;33:2217-21. https://doi.org/10.1007/s00464-018-6507-3 20. Linhares J, Hatschbach S, Tsunoda A, Groth A. To Boldly Go Where No Man Has Gone Before. Mastology. 2019;29(1):2-3. https:doi.org/10.29289/2594539420190000463